Cinema 4D Essential Training: 6 HyperNURB Modeling and Sculpting. - Garrott, Rob (linkedin.com, 2012)
Introduces two CINEMA 4D modeling techniques: HyperNURBS, or subdivision modeling, for creating smooth rounded objects, and sculpting.